Histochemical study and immunotyping of thymus leukocytic populations of alpacas (Vicugna pacos) younger than 60 days of age - Grandez R., Ricardo (2019)
The objective of the study was to identify leukocyte populations in the postnatal thymus of alpacas under 60 days of age. Euthanasia was performed on six Huacaya alpacas in Huanta province, Ayacucho, Peru. Thymus samples were obtained, embedded in OCT and immediately frozen in liquid nitrogen and stored at -70 ºC until processing. Frozen sections were prepared and mounted with organosilane. Immunohistochemistry was performed with mouse primary antibody and rabbit secondary antibodies. The reaction was evidenced using the avidin-biotin-peroxidase complex and was counter-stained with hematoxylin. Specific monoclonal antibodies were used for the identification of leukocytic subpopulations of the thymus. Five visual fields were randomly evaluated at 400X. The distribution and density of the staining was classified as negative (-), inconstant (±), slight (+), moderate (++) and strong (+++). The results show that the largest population of leukocyte cells was located in the cortex of the thymus and corresponded to immature cells that do not express surface markers; likewise, the highest population of immunomarked cells, in maturation, were located in the medulla of the thymus, predominantly the TCR-αβ lymphocytes, with low values ​​of γδ TCR lymphocytes, CD8 lymphocytes, B lymphocytes and monocytes/macrophages, with inconstant lymphocyte values CD4. In the cortex of the thymus there were low values ​​of αβ TCR lymphocytes and CD8 lymphocytes, and inconstant values ​​of monocytes/macrophages, without evidence of γδ TCR lymphocytes, CD4 lymphocytes and B lymphocytes.